1997
DOI: 10.1074/jbc.272.30.18608
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding Properties of Human Hsp90

Abstract: Hsp90 is one of the most abundant proteins in the cytosol of eukaryotic cells. Under physiological conditions Hsp90 has been shown to play a major role in several specific signaling pathways, including maturation of various kinases and maintenance of steroid receptors in an activable state. It is well established that the level of Hsp90 increases severalfold under stress conditions, and it has been shown that the chaperone function of Hsp90 is ATP-independent. Although yeast Hsp90 does not bind ATP, as determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 52 publications
(47 reference statements)
4
76
0
2
Order By: Relevance
“…It has been reported that Hsp90 cannot bind strongly to adenine-modified nucleotide analogs, but interacts with ribose-modified ATP with an affinity comparable to that of unmodified ATP [6]. Therefore we studied the interaction of differently substituted nucleotides with Hsp90.…”
Section: Interactions Of Nonhydrolyzable Nucleotides With Hsp90mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that Hsp90 cannot bind strongly to adenine-modified nucleotide analogs, but interacts with ribose-modified ATP with an affinity comparable to that of unmodified ATP [6]. Therefore we studied the interaction of differently substituted nucleotides with Hsp90.…”
Section: Interactions Of Nonhydrolyzable Nucleotides With Hsp90mentioning
confidence: 99%
“…On the contrary, it does not show a significant interaction with GTP, pirimidine nucleotides, and nucleotides in which the ribose-2¢-OH position has been substituted (TNP, ribose-attached resin; phosphate in NADP). The integrity of the adenine ring is also important for binding, since Hsp90 does not bind to C8-linked ATPresins under stringent conditions ( [6,13]; Cs. S} o oti and P. Csermely, unpublished observations), and a substitution at the 6-adenine position (e.g.…”
Section: Nucleotide Binding To the N-terminal Domain Of Hsp90mentioning
confidence: 99%
See 3 more Smart Citations